Personality traits and their effects among university students in Malaysia: a systematic review - Yong, Claudia; Nor Zainudin, Zaida; Mohd Anuar, Mohd Ashraff; Wan Othman, Wan Norhayati (Human Resources Management Academic Research Society (HRMARS), 2022)
Personality traits have been consistently proven to have an extent of influence on individual’s behavior, emotion, and cognition. In the university setting, various studies noted different personality traits predispose students to varied academic preference and performance, decision making styles, probability of obtaining a university degree, and furthermore, happiness. The purpose of this review was to explore how university students’ personality traits were investigated in past research and the effects that comes with different personality traits. Precisely, this literature review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies which assigned personality traits as an independent variable among university students in Malaysia and published from the year 2013 to 2022 were included. The initial search retrieved 668 articles, with 21 articles included in this review. Summarily, this review found evidence that personality traits are not limited to The Big-Five categories as personality traits have been investigated within different epistemologies. Within the context of university students in Malaysia, personality traits predispose certain outcomes such academic performance, motivation, coping strategies, language learning, level of stress, and happiness. These outcomes, however, could be influenced by other underlying affects and mediators. This review could provide utility to university students, tertiary educational institutions, mental health institutions and other related bodies not only in the assessment of personality traits and their effects, but also in recognizing personality traits as one of university students’ inextricable assets.